2015
DOI: 10.1007/s00256-014-2092-2
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, imaging findings, risk factors, and long-term sequelae of distal clavicular osteolysis in young patients

Abstract: In athletic teenagers, the combination of weightlifting and overhead activity is a risk factor for atraumatic DCO, and females are affected in 24 %. Long-term sequelae include widening of the AC joint and AC joint osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…Bone marrow edema and early osteoarthritis at the elbow, known as posteromedial impingement (6), and at the shoulder (26,27) are seen as sequelae of abnormal biomechanical stress in overhead athletes, even at a young age. For the diagnosis of posteromedial elbow impingement in baseball players, a smaller previous study by Cohen et al (6) showed good correlation between MR arthrography and arthroscopy.…”
Section: Myotendinous Injuriesmentioning
confidence: 99%
“…Bone marrow edema and early osteoarthritis at the elbow, known as posteromedial impingement (6), and at the shoulder (26,27) are seen as sequelae of abnormal biomechanical stress in overhead athletes, even at a young age. For the diagnosis of posteromedial elbow impingement in baseball players, a smaller previous study by Cohen et al (6) showed good correlation between MR arthrography and arthroscopy.…”
Section: Myotendinous Injuriesmentioning
confidence: 99%
“…With very little mention in the pediatric literature, Roedl et al recently reported that atraumatic distal clavicular osteolysis occurs in 6.5% of adolescents between 13 and 19 years of age presenting with atraumatic shoulder pain. 70 The study found that overhead sports such as swimming, basketball, volleyball, and tennis, especially when combined with weight training, was the strongest risk factor in adolescents due to frequent tension and traction by the strong acromioclavicular and coracoclavicular ligaments on the relatively weak distal clavicle. Different than adults, where distal clavicular osteolysis is virtually seen exclusively in males, in adolescents, 24% of affected patients were female.…”
Section: Distal Clavicular Osteolysismentioning
confidence: 99%
“…AODC is characterized by chronic changes seen in the lateral end of the clavicle. It is seen most commonly in those engaged in body building and competitive weight lifting (21). Less commonly such lesions have been reported in athletes involved in basketball, volleyball, swimming, football, and baseball pitchers (21).…”
Section: Atraumatic Osteolysis Of the Distal Clavicle (Aodc)mentioning
confidence: 99%
“…Athletes participating in sports that require overhead activity as well as supplemental weight training are at a higher risk. AODC is believed to be due to repetitive excess load and associated microtrauma to the distal end of the clavicle (21).…”
Section: Atraumatic Osteolysis Of the Distal Clavicle (Aodc)mentioning
confidence: 99%